Global warming, carbon cycles, forests and photosynthesis; a hypothesis for global cooling - John, Jacob E. (Frontiers in Earth Science, 2025)
In relation to global warming and the role of carbon dioxide, the atmospheric residence-time of carbon dioxide from industrial emissions, and the carbon dioxide fixation capacity by photosynthesis in forests, land areas and oceans is considered, for the decades 1960 to 2010. Carbon dioxide fixation in forests, annually and worldwide, is estimated to be larger than the annual and global carbon dioxide emissions from industrial and land use activities, for the decades 1960 to 2010. Observations of the Keeling curve for the period 1960 to 2010, imply slow and rate-limiting steps for the atmospheric carbon dioxide cycle from industrial emissions, namely the transfer of carbon dioxide from the atmosphere to the Earth’s surface, forests, land areas and oceans. It is proposed that these carbon dioxide emissions have a long residence-time with significant accumulation in the atmosphere. Carbon dioxide emissions from natural-biological sources, namely respiration of organisms and passive emissions from the land and oceans, remain close to the Earth’s surface, with short atmospheric residence-times, rapid conversion into biomass and no significant accumulation in the atmosphere. This is known as the natural carbon dioxide cycle. Research and development are proposed as follows; (a) determination of the atmospheric residence times of industrial, urban and natural carbon dioxide emissions, (b) effective cooling of flue gases from industrial emissions to direct these emissions to lower atmospheric altitude(s), and thereby decrease the atmospheric residence-time(s) of carbon dioxide and (c) synthetic hydrocarbon fuels for aircraft, which are low-carbon in the complete cycle, developed with public-funded research. Global, public-funded research and development programs are proposed for achieving these goals, involving national and international organisations and industries.